Dentists’ perception of health risk associated with cigarettes and alternative tobacco products: A descriptive study - Bangera, Danavanthi S; Takana, Mohamed Tahir; Gopakumar, Aji; Muttappallymyalil, Jayakumary (Nepal Journal of Epidemiology, 2022)
Cigarettes and alternative tobacco products cause various oral health issues ranging from minor tooth decay/gum-diseases to oral cancer. According to CDC, over 40% adult cigarette smokers have reported untreated tooth decay which later leads to severe oral health problems. The study intended to find the impact of dentists’ perceived risk of smoking various tobacco products on their attitude and practice toward tobacco cessation advice. The study was conducted using a cross-sectional design. Data was collected on the perception of dentists who are smokers, regarding smoking-related health risks involved in various tobacco products. Dentists’ attitude was measured using a questionnaire with a 5-point rating scale and a practice list of items with a 3-point rating scale. Descriptive/inferential techniques were applied, significance level was fixed at 5%. Among the 31 tobacco users, 80.6% of dentists perceived severe risk with cigarette use compared to alternative tobacco products (71%). Positive attitude and good practice were observed among those who perceived severe risk, however, no statistical significance was observed (Fisher’s exact test, p-value >0.05). The study concluded that young dentists, males, Arab nationals, highly educated and specialists had a positive attitude toward smoking cessation activities. Among the smokers, dentists recognize their role and responsibility very seriously in building a smoke-free community, but their risk perception and good attitude did not positively reflect on their clinical practice in smoking cessation programs. Though the dentists had a better perception and attitude towards smoking cessation, their clinical practice in offering advising sessions is inversely related to their perception/attitude.